Love of God and Love of Neighbor in the Theology of Karl Rahner and Karl Barth - Molnar, Paul D. (Modern theology, 2004)
The way Barth and Rahner envision the relationship between the commands to love God and neighbor is affected by their views of the relationship between the immanent and economic Trinity. Rahner identifies the immanent and economic Trinity; thinks the two commands are identical, and believes that self-acceptance is the same as accepting Christ and revelation. Barth insists that, while identical in content, the immanent and economic Trinity must be sharply distinguished without separation; insists the two commands are inseparable but not identical and maintains that we must seek God only in Christ. This divergence, I contend, results from their very dissimilar understandings of nature and grace and is rooted in their different starting points for theology, namely, transcendental experience for Rahner and God's Word and Spirit for Barth.